2013
DOI: 10.3329/seajph.v2i1.15254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of socio-demographic characteristics on the prevalence of anemia among school going adolescent girls in Lucknow district, India

Abstract: Anemia is a serious public health concern in most developing countries and the prevalence of anemia is quite high among adolescent girls.  A cross-sectional descriptive study was carried out among school going adolescent girls in urban as well as rural schools of the Lucknow district, Uttar Pradesh, India from October 2008 to September 2009 with the objectives of studying the prevalence of anemia and the various socio-demographic characteristics in relation to anemia. Multistage random sampling was used to sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 0 publications
2
14
1
Order By: Relevance
“…A study done in wayanad district found to be more 96.5% but in the present study there was lower prevalence compared to other studies and similar studies reported in Tamil nadu 8 and Andra Pradesh 7 as 58.4% and 77.3% the prevalence in Wayanad district prevalence of mild anaemia was 30.5%, and that of severe was 10.1% that of moderate anaemia was 55.9%. 10 Similar prevalence is reported by CMS Rawat et al 11 at Meerut. A higher prevalence was noted by J Rajaratnam et al 12 in Tamil Nadu.…”
Section: Discussionsupporting
confidence: 78%
“…A study done in wayanad district found to be more 96.5% but in the present study there was lower prevalence compared to other studies and similar studies reported in Tamil nadu 8 and Andra Pradesh 7 as 58.4% and 77.3% the prevalence in Wayanad district prevalence of mild anaemia was 30.5%, and that of severe was 10.1% that of moderate anaemia was 55.9%. 10 Similar prevalence is reported by CMS Rawat et al 11 at Meerut. A higher prevalence was noted by J Rajaratnam et al 12 in Tamil Nadu.…”
Section: Discussionsupporting
confidence: 78%
“…It may be due to the fact that breakfast was the most commonly skipped meal among girls of these age group. The findings of this study are similar with the findings of Tripathi et al and Ahmad et al 7,8 Mean height of adolescent school girls by age Similar to the weight, in both urban and rural adolescent school girls mean height was significantly higher than ICMR mean height for respective ages. The mean height of adolescent girls in both urban and rural schools was better than ICMR standards except in age 13, 14, 15, 16 17, 18 and 19 years in both urban and rural schools.…”
Section: Mean Weight Of Adolescent School Girls By Agesupporting
confidence: 82%
“…Almost similar to the study conducted by Sachan et al who reported that (40.3%) of girls belonged to SES III. 8 My study revealed that in urban school girls maximum (38.2%) number of girls belonged to SES II while in rural school girls maximum (55.2%) number of girls belonged to SES III. This finding is concomitant to the results of Sachan et al who observed that a higher percentage of girls belonged to SES II (38.6%) and to SES III (59.8%) in urban and rural schools respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently the overall household income directly affects the quality of diet, nutritional status and hygiene adversely. Jhondale et al 7 and B. Sachan 16 reported the incidence of anemia to be maximum in the poorer sections of the society. In the study by S.Kaur et al 11 , the girls with grade V status were associated with increased likelihood of anemia (O.R.…”
Section: Discussionmentioning
confidence: 98%